Impermeable material as well as preparation method, construction process and application thereof

By using anti-seepage materials with components such as copper tailings and bentonite, the resource dependence and environmental risks of anti-seepage technology in solid waste treatment are solved, and efficient, economical and environmentally friendly anti-seepage effects are achieved.

CN119841582APending Publication Date: 2025-04-18BEIJING MINING & METALLURGICAL TECH GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510234148.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The anti-seepage technology in existing solid waste treatment faces the problems of resource dependence, construction limitations and high costs, and has failed to make full use of bulk industrial solid waste such as copper tailings, which poses environmental risks.

Method used

The anti-seepage materials are made of copper tailings, bentonite, xanthan gum, PAM, lime, gypsum and water as the main components. Through the synergy of multiple components, the anti-seepage performance and environmental safety are improved.

Benefits of technology

The resource utilization of copper tailings has been achieved, which significantly improves the anti-seepage performance and environmental safety, reduces construction costs, and meets the requirements of environmental protection and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841582A_ABST
    Figure CN119841582A_ABST
Patent Text Reader

Abstract

The invention provides an anti-seepage material as well as a preparation method, a construction process and application thereof. Relates to the technical field of solid waste treatment. Wherein the impermeable material comprises copper tailings, bentonite, xanthan gum, PAM, lime, gypsum and water. According to the anti-seepage material, through the synergistic effect of multiple components, resource utilization of the copper tailings is achieved, meanwhile, the anti-seepage performance and the environmental safety are remarkably improved, and the anti-seepage material has wide application prospects and important environmental significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid waste treatment, and in particular to an anti-seepage material and a preparation method, a construction process and an application thereof. Background Art

[0002] In the field of solid waste treatment, with the acceleration of industrialization and urbanization, the amount of solid waste generated continues to increase, and its treatment and disposal has become an environmental problem that needs to be solved urgently. Solid waste treatment technology aims to achieve waste reduction, harmlessness and resource utilization through scientific and reasonable means to reduce the negative impact on the environment and improve resource utilization efficiency. Among them, anti-seepage technology is an important link in solid waste treatment, especially in places such as solid waste dumps, landfills and tailings ponds. Preventing harmful substances from leaking into the soil and groundwater is the key to ensuring environmental safety.

[0003] In the prior art, natural clay and artificial synthetic materials are commonly used anti-seepage materials. Natural clay is widely used because of its low cost and convenient construction conditions, but its application is limited by the distribution of clay resources. In areas where clay resources are scarce, the use of natural clay as an anti-seepage material is not only costly, but also difficult to meet the requirements of the thickness and compactness of the anti-seepage layer. In addition, natural clay is a non-renewable resource, and its large-scale use will lead to a waste of land resources. Artificial synthetic anti-seepage materials, such as HDPE anti-seepage membranes, although they have good anti-seepage performance, are relatively expensive and have strict environmental conditions and process requirements during construction, which limits their application in large-scale projects.

[0004] However, existing anti-seepage materials have many defects in practical applications. Although the permeability coefficient of the natural clay anti-seepage layer can reach the standard of "General Industrial Solid Waste Storage and Landfill Pollution Control Standard" (GB18599-2020) of no more than 1.0×10 -5 cm / s requirement, but is limited by the thickness that needs to be greater than 0.75m, resulting in a high demand for resources. Due to the limited natural clay resources in some areas, the construction cost is pushed up. In addition, the construction process of natural clay is complicated and requires thickening and compaction, which increases the project cost and construction difficulty. The artificial synthetic anti-seepage material HDPE membrane has defects such as easy deformation, aging, and breakage. At the same time, some tailings-based anti-seepage materials fail to fully consider the solidification of sulfides and heavy metals in the tailings, and there are potential environmental risks. In addition, the comprehensive utilization rate of copper tailings in the existing technology is low, and a large amount of tailings are idle or piled up, which not only occupies land resources, but also may pollute the environment.

[0005] In summary, the existing anti-seepage technology in solid waste treatment faces many challenges. The resource dependence and construction limitations of natural clay, as well as the high cost and environmental adaptability of artificial synthetic materials, limit their application in large-scale projects. At the same time, the existing technology fails to make full use of bulk industrial solid wastes such as copper tailings, which not only wastes resources, but also fails to effectively solve the environmental risks of tailings. Therefore, the development of an economical, efficient and environmentally friendly new anti-seepage material to replace traditional anti-seepage materials and realize the resource utilization of solid waste is an urgent problem to be solved in the current field of solid waste treatment.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide an anti-seepage material and a preparation method, a construction process and an application thereof. The anti-seepage material, through the synergistic effect of multiple components, significantly improves the anti-seepage performance and environmental safety while realizing the resource utilization of copper tailings, and has broad application prospects and important environmental significance.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] In a first aspect, the present invention provides an anti-seepage material, which comprises copper tailings, bentonite, xanthan gum, PAM, lime, gypsum and water.

[0010] In an optional embodiment, the anti-seepage material includes the following components in parts by weight:

[0011] Copper tailings, 90-95 parts;

[0012] Bentonite, 4 to 6 parts;

[0013] Xanthan gum, 0.5 to 1 part;

[0014] PAM, 0.01 to 0.1 parts;

[0015] Gypsum, 0.5 to 1.0 parts;

[0016] Lime, 0 to 1 part;

[0017] Water, 10 to 20 parts.

[0018] In an optional embodiment, the copper tailings are fine-grained copper tailings;

[0019] The fine-grained copper tailings have the following characteristics:

[0020] A. Average particle size is 0.019mm~0.03mm;

[0021] B. The dry weight content of particles smaller than 0.019 mm is greater than 20%, and the dry weight content of particles larger than 0.074 mm is greater than 50%;

[0022] C. The moisture content of the fine-grained copper tailings is lower than 15%.

[0023] In an optional embodiment, the bentonite is sodium bentonite.

[0024] In an optional embodiment, the CaO content in the lime is greater than 80%.

[0025] In an optional embodiment, the xanthan gum is an instant xanthan gum with a particle size of 80 meshes.

[0026] In an alternative embodiment, the pH of the water is 4-11.

[0027] In a second aspect, the present invention provides a method for preparing the anti-seepage material as described in any one of the aforementioned embodiments, comprising:

[0028] Mixing PAM with water to prepare a PAM solution;

[0029] The copper tailings, bentonite, xanthan gum, lime and gypsum are mixed to obtain a mixture;

[0030] The mixed material and the PAM solution are stirred and mixed to obtain an anti-seepage material.

[0031] In a third aspect, the present invention provides a construction process of the anti-seepage material as described in any one of the aforementioned embodiments, comprising:

[0032] The copper tailings, bentonite, xanthan gum, PAM, lime, gypsum and water are mixed to obtain an anti-seepage material slurry;

[0033] The anti-seepage material slurry is poured on the slope area and / or bottom area of ​​the solid waste storage site, and is subjected to manual and / or mechanical rolling treatment to achieve a compaction degree of not less than 80% to form an anti-seepage layer.

[0034] In a fourth aspect, the present invention provides a use of the anti-seepage material as described in any of the aforementioned embodiments in the preparation of an anti-seepage treatment product in a solid waste storage site.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The anti-seepage material of the present invention is mainly composed of copper tailings, bentonite, xanthan gum, PAM, lime, gypsum and water, and has many significant beneficial effects. First, the material makes full use of the large industrial solid waste of copper tailings to achieve efficient recycling of resources. As a kind of fine-grained mineral waste, copper tailings itself has certain particle characteristics and filling effects, but in traditional applications, it is often difficult to be directly used in the field of anti-seepage due to its high permeability coefficient. By adding bentonite, the permeability coefficient of the material can be significantly reduced by utilizing its high expansibility and good dispersibility, thereby improving the anti-seepage performance. Studies have shown that the addition of bentonite can effectively fill the pores between the copper tailings particles to form a dense anti-seepage structure.

[0037] Secondly, the introduction of xanthan gum and PAM further optimizes the performance of the material. As a natural high molecular polymer, xanthan gum has good thickening and bonding properties, which can enhance the cohesion between particles, improve the material's crack resistance, and maintain a stable anti-seepage effect under complex environmental conditions. PAM forms a stable three-dimensional network structure through its bridging effect, further enhancing the material's mechanical properties and anti-seepage ability. This composite modification method not only improves the material's anti-seepage performance, but also makes it more adaptable to construction.

[0038] In addition, the addition of lime and gypsum brings significant environmental friendliness to the material. Lime can react chemically with sulfides in copper tailings to generate stable calcium sulfate, thereby solidifying harmful substances, sulfides or heavy metals in the tailings and reducing their potential risks to the environment. Gypsum can work in synergy with lime to further stabilize heavy metal ions and prevent them from migrating and releasing in the environment. This chemical solidification not only improves the material's anti-seepage performance, but also effectively fixes harmful substances in copper tailings, meeting the requirements of environmental protection and sustainable development.

[0039] In summary, the anti-seepage material of the present invention, through the synergistic effect of multiple components, realizes the resource utilization of copper tailings while significantly improving the anti-seepage performance and environmental safety, and has broad application prospects and important environmental significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0041] Figure 1 The method for preparing the anti-seepage material in the embodiment of the present application;

[0042] Figure 2 This is a graph showing the copper tailings particle size test results used in the comparative test example of this application. DETAILED DESCRIPTION

[0043] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0044] In an embodiment of the present application, an anti-seepage material is provided, wherein the anti-seepage material includes copper tailings, bentonite, xanthan gum, PAM, lime, gypsum and water.

[0045] The above-mentioned copper tailings are composed of finely divided sand particles after natural copper ore is processed by mineral processing. The main components include non-metallic minerals such as quartz, feldspar, illite, mica, etc. The metal minerals may include chalcopyrite, chalcocite, magnetite, hematite, etc.

[0046] It should be noted that according to the "China Bulk Industrial Solid Waste Comprehensive Utilization Industry Development Report" (2020-2021), in 2020, my country's tailings production was 1.295 billion tons, and the tailings utilization was 441 million tons, with a utilization rate of only 34.05%. Compared with solid wastes such as coal gangue and fly ash with a comprehensive utilization rate of over 70%, my country's tailings comprehensive utilization rate is relatively low. In addition, according to public literature, from 2011 to 2020, my country's copper tailings production and discharge were second only to iron tailings, with a total production and discharge of about 3.25 billion tons, but the utilization rate of copper tailings was only 8.4%. On the other hand, the current comprehensive utilization of fine-grained copper tailings at home and abroad is mainly used as underground filling materials and preparation of building materials. However, the use of underground filling materials is limited by whether there are goafs that need to be backfilled in the area, and the use of building materials will add a lot of additional transportation costs and transportation risks. Therefore, it is of great significance to expand the comprehensive utilization of copper tailings.

[0047] Copper tailings, as an important industrial by-product, has abundant reserves and low comprehensive utilization rate. In the preparation of anti-seepage materials, copper tailings can be used as a key skeleton material. Through its unique physical properties, it can significantly enhance the stability and overall structural performance of the material, providing strong support for the material. At the same time, the rational use of copper tailings can effectively improve the permeability of the material and achieve precise control of the permeability. In addition, the use of copper tailings to prepare anti-seepage materials not only helps to solve the problem of low utilization rate, but also can significantly reduce material costs in large-scale applications, showing good economy and environmental friendliness.

[0048] The anti-seepage materials also include auxiliary materials and additives such as xanthan gum, PAM, lime, gypsum, and bentonite.

[0049] The above-mentioned bentonite is a natural clay mineral rich in montmorillonite, which has strong water absorption and expansion. In anti-seepage materials, bentonite mainly plays the role of closing pores and reducing water penetration. Bentonite can effectively prevent water penetration and form a dense waterproof layer. Its characteristic of swelling after absorbing water makes it show excellent anti-seepage performance underwater or in a humid environment.

[0050] Xanthan gum is a natural polysaccharide, commonly used as a thickener or stabilizer. In anti-seepage materials, it is mainly used as a thickener to adjust the fluidity of the material and enhance adhesion and stability. Xanthan gum can enhance particle cohesion, improve crack resistance, improve the viscosity and rheological properties of the material, thereby enhancing its operability during construction and improving the stability of the anti-seepage layer.

[0051] PAM (polyacrylamide) is a polymer chemical substance widely used in water treatment, soil improvement and other fields. In anti-seepage materials, PAM can be used as a thickener and flocculant to help the material form a better structure and enhance the cohesion of the soil. PAM plays a bridging role in anti-seepage materials, forming a stable three-dimensional network structure, and helps to improve the sealing of the anti-seepage layer and reduce water penetration. During the application process, it can improve the physical properties of the material and enhance its stability in various environments.

[0052] Lime is a building material that is mainly used for soil improvement and reinforcement. In anti-seepage materials, lime is often used to increase the strength and stability of soil and help adjust and stabilize the pH value of soil. Lime can react with organic matter or other minerals in the soil to form a stronger structure, reduce water permeability, and solidify sulfides (forming CaSO 4 ). In addition, it can neutralize the acidic components in the soil (stabilize pH) and improve the durability of the soil.

[0053] Gypsum is a mineral used in construction and industrial materials. In anti-seepage materials, gypsum can increase the strength and waterproof performance of the material. Gypsum can react with water to form a hardening substance and synergistically solidify heavy metals (such as PbSO 4 precipitation), enhance the structural strength of the material, and to a certain extent can improve the stability and durability of the anti-seepage material.

[0054] Water is an essential solvent and medium in anti-seepage materials. When mixing other ingredients, water can help form a uniform slurry or solution and enable other ingredients to react or fuse better. The role of water in anti-seepage materials is not only to provide fluidity, but also to promote the reaction of various components, thereby helping to form a stronger waterproof layer.

[0055] In summary, these materials work together on the anti-seepage layer. Copper tailings and bentonite are mainly responsible for enhancing the structural stability and anti-seepage performance of the material; xanthan gum and PAM optimize the adhesion and fluidity of the material; lime and gypsum are used to enhance strength and improve chemical properties; water is a solvent and reaction medium. Through the combined effect of these components, the performance of the anti-seepage material can be effectively improved, ensuring its long-term effectiveness and stability in waterproofing and anti-seepage.

[0056] These materials are likely to produce certain synergistic effects during the preparation process and use, promoting each other's performance improvement.

[0057] First, copper tailings can be used as a skeleton material to provide structural support, while bentonite fills the pore channels of copper tailings by absorbing water and swelling, reducing the permeability coefficient and forming a denser structure. This synergistic effect enhances the overall stability and sealing of the anti-seepage layer, further reducing water penetration.

[0058] Secondly, xanthan gum and bentonite interact with each other, and xanthan gum can improve the water retention and resistance of the material. It should be noted that xanthan gum inhibits the cracking of expansive soil in two ways. On the one hand, it forms a "bridge" structure with soil particles through bonding and cementation, which enhances the tensile strength of the soil as a whole; on the other hand, it blocks the contact between water and soil particles through filling and film-forming effects, reducing the thickness of the hydration film of clay minerals.

[0059] Thirdly, PAM, as a thickener, can further improve the adhesion and fluidity of anti-seepage materials when used in combination with xanthan gum. PAM can also promote the aggregation and flocculation of water, so that the material forms a denser layered structure during the anti-seepage process, thereby improving the overall sealing performance. In addition, bentonite and PAM polyacrylamide will interact in water, thereby improving the hydrophilicity of bentonite, increasing the viscosity of bentonite, avoiding agglomeration and precipitation, and thus reducing the permeability coefficient.

[0060] Lime has strong alkalinity and can react with the acidic components in bentonite to neutralize it and adjust the pH value of the soil, thereby promoting better expansion of bentonite and significantly improving the sealing of anti-seepage materials. At the same time, in anti-seepage materials, the presence of lime can release calcium ions. These calcium ions can reduce the viscosity reduction of xanthan gum solution under acidic or high temperature conditions (such as the presence of acidic leaching water in some solid storage sites or the sulfur in copper tailings has acid-generating potential), thereby improving its acid resistance and heat resistance. In addition, xanthan gum, as a thickener and stabilizer, can be compounded with lime-based materials to improve the fluidity and anti-sedimentation properties of the slurry and enhance the overall structure and durability of the material. This synergistic effect shows good crack resistance and durability in anti-seepage materials, further improving the overall performance of the material.

[0061] Both lime (CaO) and gypsum (CaSO·2H O) can adjust the pH value of the material and provide a suitable alkaline environment for the anti-seepage material. In addition, when lime and gypsum are mixed with bentonite, the compressive strength of the material can be significantly improved. This enhancement is mainly due to the chemical properties of lime and gypsum and their interaction with bentonite. The alkalinity of lime can improve the expansion properties of bentonite, while gypsum enhances the overall structural stability of the material through its hardening properties. When the two are used in combination, the durability of the anti-seepage layer can be further improved, so that it exhibits good water resistance and mechanical properties under complex environmental conditions.

[0062] In addition, in terms of the interaction between water and other components, water plays an important role as a solvent between these materials. It not only promotes the expansion of bentonite and the dissolution of xanthan gum and PAM. The addition of water enables these components to be evenly mixed and form the required slurry or solution, thereby effectively improving the anti-seepage effect.

[0063] In short, these materials can indeed produce synergistic effects during the preparation process, especially in terms of complementary physical and chemical properties, which helps to improve the performance of anti-seepage materials. For example, bentonite and xanthan gum can jointly optimize fluidity and adhesion, PAM and xanthan gum can increase the cohesion of the material and enhance the structural stability, while lime and gypsum can further improve the compressive strength of the material through solidification. Ultimately, these synergistic effects can ensure the efficiency, stability and durability of anti-seepage materials during use.

[0064] In some embodiments, the anti-seepage material includes the following components in parts by weight:

[0065] Copper tailings, 90 to 95 parts; for example, it can be 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, etc.

[0066] Bentonite, 4 to 6 parts; for example, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, etc.

[0067] Xanthan gum, 0.5 to 1 part; for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, etc.

[0068] PAM, 0.01 to 0.1 parts; for example, it can be 0.01 parts, 0.02 parts, 0.03 parts, 0.05 parts, 0.08 parts, 0.1 parts, etc.

[0069] Gypsum, 0.5 to 1.0 parts; for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, etc.

[0070] Lime, 0 to 1 part; for example, it can be 0 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part, 1 part, etc.

[0071] Water: 10 to 20 parts; for example, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, etc.

[0072] It should be noted that in the anti-seepage material provided in the embodiment of the present application, copper tailings account for a large proportion (at least more than 90%), that is, at least 900kg of copper tailings will be consumed to prepare 1 ton of synthetic materials. According to the "Pollution Control Standards for General Industrial Solid Waste Storage and Disposal Sites" (GB18599-2020), the thickness of the clay layer in Class I sites should be no less than 0.75m. Assuming that the anti-seepage material in this embodiment is used for an area of ​​200,000 m 2 If the Class I solid waste dump is treated for seepage prevention, then a rough calculation would consume at least 90,000 tons of copper tailings and save 150,000 m 3 Natural clay resources. In addition, by using the anti-seepage material in this embodiment, the laying thickness can reach 40cm to 50cm of the anti-seepage layer under the premise of meeting the requirements, which further reduces the construction cost compared with the conventional technology.

[0073] The anti-seepage material provided in this embodiment has copper tailings as the main component (more than 90%). Considering that copper tailings often contain sulfides and heavy metals, the sulfides and heavy metals that may be contained in the copper tailings are solidified by adding lime and gypsum. Therefore, the anti-seepage material in this embodiment breaks through the limitations of traditional anti-seepage materials that rely on natural resources or high-cost synthetic materials through the synergistic effect of copper tailings substrate modification and composite additives, and achieves the triple goals of solid waste resource utilization, anti-seepage performance compliance, and controllable environmental risks. Its technical solution has clear innovation, practicality and promotion value, and meets the requirements of the "General Industrial Solid Waste Storage and Landfill Pollution Control Standard" (GB18599-2020).

[0074] In some embodiments, the copper tailings are fine-grained copper tailings.

[0075] The fine-grained copper tailings have the following characteristics:

[0076] A. Average particle size is 0.019mm~0.03mm;

[0077] B. The dry weight content of particles smaller than 0.019 mm is greater than 20%, and the dry weight content of particles larger than 0.074 mm is greater than 50%;

[0078] C. The moisture content of the fine-grained copper tailings is lower than 15%.

[0079] In some embodiments, the bentonite is sodium bentonite. Bentonite refers to a hydrated clay mineral mainly composed of montmorillonite, preferably sodium bentonite.

[0080] It should be noted that sodium bentonite is a natural bentonite containing a large amount of sodium ions. Bentonite is a clay mineral mainly composed of montmorillonite, which has very strong water absorption and expansion properties.

[0081] In some embodiments, the CaO content in the lime is greater than 80%.

[0082] In some embodiments, the xanthan gum is instant xanthan gum with a particle size of 80 meshes.

[0083] In some embodiments, the pH of the water is 4 to 11. The water may be tap water.

[0084] refer to Figure 1 In an embodiment of the present application, a method for preparing an anti-seepage material as described in any one of the aforementioned embodiments is provided, comprising:

[0085] Step S1, mixing PAM with water to prepare a PAM solution;

[0086] Step S2, mixing the copper tailings, bentonite, xanthan gum, lime and gypsum to obtain a mixture;

[0087] Step S3, stirring and mixing the mixed material and the PAM solution to obtain an anti-seepage material.

[0088] Among them, the preparation of the anti-seepage material can be made of fine-grained copper tailings as the main component, mixed with sodium-based bentonite (sodium calcium-based bentonite can be used), PAM, xanthan gum, lime, and gypsum, and mixed evenly to obtain a mixture. Specifically, in this embodiment, a PAM solution and a mixture are prepared separately. The mixture and the PAM solution are stirred to obtain the novel artificial synthetic anti-seepage material in this embodiment. The above steps S1 and S2 can be processed in advance at any one step, or can be carried out simultaneously.

[0089] In an embodiment of the present application, a construction process of the anti-seepage material as described in any of the above embodiments is provided, including:

[0090] Step S100, mixing copper tailings, bentonite, xanthan gum, PAM, lime, gypsum and water to obtain an anti-seepage material slurry;

[0091] Step S200, pouring the anti-seepage material slurry on the slope area and / or bottom area of ​​the solid waste storage site, using manual rolling and / or mechanical rolling to make the compaction degree reach not less than 80%, so as to form an anti-seepage layer.

[0092] In an embodiment of the present application, there is provided an application of the anti-seepage material as described in any one of the aforementioned embodiments in preparing an anti-seepage treatment product in a solid waste storage site.

[0093] The present invention is further described below by means of specific examples, but it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.

[0094] Table 1. Dosage of each component of the anti-seepage material in the examples and comparative examples

[0095] Components Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Copper tailings 90 92 91 94 95 50 / Bentonite 6 4 5 4 4 6 / Xanthan gum 1 0.6 0.8 0.5 0.5 1 / PAM 0.1 0.01 0.05 0.08 0.07 0.1 / plaster 1 0.5 1 0.6 0.8 1 / lime 1 0.5 0 0.8 1 1 / Mixture 99.10 97.60 97.85 99.98 101.37 59.10 / water 16 13 13 17 15 16 / Water-cement ratio 0.16 0.13 0.13 0.17 0.15 0.27 / natural clay / / / / / / √

[0096] Example 1

[0097] In this embodiment, the following method is used for preparation and construction.

[0098] 1. Copper tailings information:

[0099] (1) Particle size of copper tailings:

[0100] The tailings from a copper mine tailings pond in Fujian are used. Figure 2 The initial average particle size of the copper tailings is 217.176 μm, d10% is 7.793 μm, and d50% is 188.884 μm. After sieving with a 75-mesh screen, the copper tailings are used to prepare a new type of artificial synthetic anti-seepage material.

[0101] (2) Analysis of copper tailings composition:

[0102] Table 2. Analysis results of copper tailings composition

[0103] Test items Proportion Test items Proportion S 3.60% Zn <0.05% As 0.01% Cu 0.06% Hg <0.0001% Fe 2.05% Pb <0.05% Cr 0.0008%

[0104] From the component analysis results in Table 2, it can be seen that the sulfur content is relatively high and the copper tailings have a certain acid production potential.

[0105] 2. Construction method:

[0106] (1) After the raw materials are naturally air-dried, the air-dried copper tailings, polyacrylamide-modified bentonite, and CaSO 4 , CaO and xanthan gum are weighed and dry-mixed evenly. For specific dosage parameters, refer to Table 1.

[0107] (2) Add a certain proportion of PAM solution and stir at a constant speed until it becomes a uniform slurry (anti-seepage material).

[0108] (3) Pour the slurry on the slope and bottom of the solid waste storage site (Class I site), use mechanical rolling to achieve a compaction degree of more than 80%, form an impermeable layer with a thickness of more than 40 to 50 cm, and maintain for 7 days.

[0109] Example 2

[0110] In this embodiment, the following method is used for preparation and construction.

[0111] Experimental methods:

[0112] The same as Example 1, except for the dosage of each component in Table 1.

[0113] Example 3

[0114] In this embodiment, the following method is used for preparation and construction.

[0115] Experimental methods:

[0116] The same as Example 1, except for the dosage of each component in Table 1.

[0117] Example 4

[0118] In this embodiment, the following method is used for preparation and construction.

[0119] Experimental methods:

[0120] The same as Example 1, except for the dosage of each component in Table 1.

[0121] Comparative Example 1

[0122] In this comparative example, the following method was adopted for preparation and construction.

[0123] Experimental methods:

[0124] The same as Example 1, except for the dosage of each component in Table 1.

[0125] Comparative Example 2

[0126] In this comparative example, natural clay was used as the anti-seepage material for construction.

[0127] Experimental methods:

[0128] Except for the anti-seepage material, the specific construction method is basically the same as that of Example 1, and the difference is the amount of each component in Table 1.

[0129] Comparative test example 1:

[0130] In this comparative test example, the permeability coefficients of different embodiments and comparative examples were investigated.

[0131] 1. Test method:

[0132] With reference to 16.3 variable head permeability test in the "Standard for Geotechnical Test Methods" (GB / T 50123-2019), a variable head permeameter was used to test the permeability coefficients of the embodiments and comparative examples.

[0133] Basic structure and parameters of variable head permeameter:

[0134] (1) Permeation container: It consists of a ring knife, a water-permeable plate, a sleeve, and upper and lower covers;

[0135] (2) Water head device: The inner diameter of the variable water head pipe should be selected according to the permeability coefficient of the sample, and should not be larger than 1 cm. The length should be more than 1.0 m, and the graduation value should be 1.0 mm;

[0136] (3) Others: soil cutter, stopwatch, thermometer, soil scraper, vaseline.

[0137] 2. Test results:

[0138] It can be seen from the test results in Table 3 below that the permeability coefficient of the anti-seepage material is smaller than that of natural clay, and the anti-seepage performance is significantly better than that of the raw copper tailings in terms of permeability coefficient.

[0139] Comparative test example 2:

[0140] In this comparative test example, environmental safety investigations were conducted on different embodiments and comparative examples.

[0141] 1. Test method:

[0142] Refer to "Toxic Leaching Method for Solid Waste In and Out: Sulfuric Acid and Nitric Acid Method" (HJ / T299-2007) to simulate the process in which harmful components in waste are leached from waste into the environment under the influence of acid precipitation when waste is disposed of in irregular landfills, stockpiled, or land used after harmless treatment.

[0143] 2. Test results:

[0144] Table 3. Permeability coefficient and environmental safety test results

[0145]

[0146] In the header of Table 3 above, "Shi" represents the short name of "Example", such as "Shi 1" being "Example 1"; "Dui" represents the comparative example of the short name, such as "Dui 1" representing "Comparative Example 1". In Comparative Example 2, all natural clay was used, and the copper tailings group used the tailings from a copper mine tailings pond in Fujian.

[0147] The test sample was taken from a copper mine tailings pond in Fujian. According to the component analysis, it was known that the tailings contained a certain amount of sulfur.

[0148] The heavy metal solidification effect was significant: the leaching concentrations of Cu and Pb in the composite material decreased by 69.7% and 62.2% respectively, indicating that the cementitious system (lime + gypsum) effectively solidified heavy metals.

[0149] The pH was successfully regulated: by adding an alkaline material (lime), the pH was increased from 6.69 to 7.3, inhibiting the risk of acidic leaching.

[0150] Compliance situation: All indicators of the composite material met the standards of industrial sewage (GB8978) and surface water class III standards (GB3838).

[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An anti-seepage material, characterized in that: The anti-seepage material comprises copper tailings, bentonite, xanthan gum, PAM, lime, gypsum and water.

2. The anti-seepage material according to claim 1, characterized in that: The anti-seepage material includes the following components in parts by weight: Copper tailings, 90-95 parts; Bentonite, 4 to 6 parts; Xanthan gum, 0.5 to 1 part; PAM, 0.01 to 0.1 parts; Gypsum, 0.5 to 1.0 parts; Lime, 0 to 1 part; Water, 10 to 20 parts.

3. The anti-seepage material according to claim 1, characterized in that: The copper tailings are fine-grained copper tailings; The fine-grained copper tailings have the following characteristics: A. Average particle size is 0.019mm~0.03mm; B. The dry weight content of particles smaller than 0.019 mm is greater than 20%, and the dry weight content of particles larger than 0.074 mm is greater than 50%; C. The moisture content of the fine-grained copper tailings is lower than 15%.

4. The anti-seepage material according to claim 1, characterized in that: The bentonite is sodium bentonite.

5. The anti-seepage material according to claim 1, characterized in that: The CaO content in the lime is greater than 80%.

6. The anti-seepage material according to claim 1, characterized in that: The xanthan gum is an instant xanthan gum with a particle size of 80 meshes.

7. The anti-seepage material according to claim 1, characterized in that: The pH of water is 4-11.

8. A method for preparing the anti-seepage material according to any one of claims 1 to 7, characterized in that: include: Mixing PAM with water to prepare a PAM solution; The copper tailings, bentonite, xanthan gum, lime and gypsum are mixed to obtain a mixture; The mixed material and the PAM solution are stirred and mixed to obtain an anti-seepage material.

9. The construction process of the anti-seepage material according to any one of claims 1 to 7, characterized in that: include: The copper tailings, bentonite, xanthan gum, PAM, lime, gypsum and water are mixed to obtain an anti-seepage material slurry; The anti-seepage material slurry is poured on the slope area and / or bottom area of ​​the solid waste storage site, and is subjected to manual and / or mechanical rolling treatment to achieve a compaction degree of not less than 80% to form an anti-seepage layer.

10. Use of the anti-seepage material according to any one of claims 1 to 7 in preparing an anti-seepage treatment product in a solid waste storage site.